37. Normal values of electrophysiological study of vision. Issue 1 (January 2015) - Tozzi, M.C.; Silipo, S.; Concon, E.; Bongiovanni, G.L.; Monaco, S.; Bertolasi, L.
<x xml:space="preserve">Abstract</x> Electroretinogram (ERG), pattern electroretinogram (PERG) and visual evoked potential (VEP) are stimulation and recording methods to evaluate the functionality of the different elements of retina and visual pathways. Objective is to define a protocol and describe normative data. 30 healthy subjects were enrolled. PEV associated with PERG, ERG in scotopic and photopic condition, the oscillatory potentials (PO) were performed. Amplitude and latency were measured. Normative values were (mean): VEP (P100): 103.79 ms, 15.81 μV; PERG (P50): 65.48 ms, 7.89 μV; scotopic ERG (wave A) 19.11 ms, 8.6 μV; (wave B) 45.26 ms, 25.55 μV; photopic ERG (wave A) 17.19 ms, 14.71 μV; (wave B) 41.19 ms, 24.51 μV; ERG -FLASH BLUE (wave A) 28.22 ms, 10.05 μV; (wave B) 63.68 ms, 51.98 μV; ERG- FLICKER: range from 31.79 to 131.83 ms, from 10.49 to 10.59 μV; oscillatory potentials PO: range from 20.7 to 50.88 ms; from 1.81 to 4.98 μV. The complete protocol allows us to explore the entire visual pathway.